Data for: Ecological comparison of native (Apis mellifera mellifera) and hybrid (Buckfast) honeybee drones in southwestern Sweden indicates local adaptation. - Schaumann, Finja; Norrström, Niclas; Niklasson, Mats; Leidenberger, Sonja (University of Skövde, 2024)
Honeybee drones’ only known task is to mate with a virgin queen. Apart from their mating behaviour, their ecology has been little studied in comparison to honeybee females. Most previous knowledge is based on direct observations at a single experimental hive and gathered during a restricted amount of time. No study has focused on differences between Apis mellifera subspecies. This study presents drone and worker bee lifetime data of Apis mellifera mellifera and Apis mellifera x (hybrid Buckfast) colonies during the whole spring and summer mating season, using the Radio Frequency Identification Technology. This method enables continuous monitoring of tagged bees at the entrance of the hives together with the individuals’ movement direction. Differences were found between Apis m. mellifera and Buckfast drones, where Apis m. mellifera showed later drone production in spring, but earlier first activities and a later peak activity. Additionally, Apis m. mellifera flew more under high light intensities and windy conditions and performed more longer flights than Buckfast drones. No differences were found in their lifespan. However, drones in general showed higher activity the higher the temperature and avoided flights in the rain.
The results confirmed that spring-born drones survive longer than summer-born drones and lived generally longer than worker bees. Drones peak activity occurred in the afternoon while worker bees showed similar activities throughout the day. Worker bees, unlike drones, did fly in the rain. Normally, orientation flights of drones are described to occur between 4 - 8 days of age, but such flights were observed earlier in this study. In summer, frequent mating flights were practiced before drones reach sexual maturity (at 12 days of age). The observed differences in drone ecology support possible local adaptation of the native subspecies Apis m. mellifera to the environmental conditions in Sweden.

Drönarnas enda kända uppgift är att para sig med en jungfrulig drottning. Bortsett från deras parningsbeteende har deras ekologi studerats lite i jämförelse med honungsbinas honor. Den mesta tidigare kunskapen är baserad på direkta observationer vid en enda experimentkupa och samlades in under en begränsad tidsperiod. Ingen studie har fokuserat på skillnader mellan underarter av Apis mellifera. I denna studie presenteras data om drönare och arbetsbins livslängd i kolonier av Apis mellifera mellifera och Apis mellifera x (hybrid Buckfast) under hela parningssäsongen på våren och sommaren, med hjälp av radiofrekvensidentifieringsteknik. Denna metod möjliggör kontinuerlig övervakning av märkta bin vid ingången till bikuporna tillsammans med individernas rörelseriktning. Man fann skillnader mellan Apis m. mellifera och Buckfast-drönare, där Apis m. mellifera visade senare drönarproduktion på våren, men tidigare första aktiviteter och en senare toppaktivitet. Dessutom flög Apis m. mellifera mer under höga ljusintensiteter och blåsiga förhållanden och utförde fler längre flygningar än Buckfast-drönare. Inga skillnader hittades i deras livslängd. Drönarna visade dock generellt högre aktivitet ju högre temperaturen var och undvek flygningar i regn.
Resultaten bekräftade att vårfödda drönare överlever längre än sommarfödda drönare och generellt sett lever längre än arbetsbin. Drönarnas högsta aktivitet inträffade på eftermiddagen medan arbetsbin uppvisade liknande aktiviteter under hela dagen. Arbetarbin, till skillnad från drönare, flög i regn. Normalt beskrivs drönarnas orienteringsflygningar inträffa mellan 4 och 8 dagars ålder, men sådana flygningar observerades tidigare i denna studie. På sommaren genomfördes frekventa parningsflygningar innan drönarna uppnådde könsmognad (vid 12 dagars ålder). De observerade skillnaderna i drönarnas ekologi stöder en möjlig lokal anpassning av den inhemska underarten Apis m. mellifera till miljöförhållandena i Sverige.
Data for: Ecological comparison of native (Apis mellifera mellifera) and hybrid (Buckfast) honeybee drones in southwestern Sweden indicates local adaptation.
Keywords: long term ecological monitoring; Species distribution; Arters utbredning; honey bees; drones (insect); Sweden; Sverige; survival; Apis mellifera; Apis mellifera; flight behaviour; RFID tags; flight activity; flygg aktivitet; honeybees; honungsbi; Drones; Drönare; survival; överlevnad; buckfast bee; buckfastbi; rfid; rfid; Apis mellifera; Apis mellifera; sweden; sverige; Sweden; Sverige; Apis mellifera mellifera; Apis mellifera x (Buckfast); Natural Sciences; Naturvetenskap; Biological Sciences; Biologi; Zoology; Zoologi; Ecology; Ekologi; Behavioural Sciences Biology; Etologi; Biota; Biologi och ekologi